Analysis and evaluation of CO and CO2 levels in the city of tacna in relation to the automotive park and environmental air quality standards - Tirado Rebaza, Leo Ulises Michaell (2021)
Air pollution in the city of Tacna, Peru, mainly attributed to its vehicle fleet, is a problem that has been evident for decades, slowly affecting the health of people, animals and the environment. The present investigation sought to determine to what extent the time of day, the places of monitoring and their interaction influence the levels of carbon monoxide (CO) and carbon dioxide (CO2) in the main points of the aforementioned city. Likewise, CO levels were compared with the Environmental Air Quality Standards according to Supreme Decree No. 003 - 2017 - MINAM (Peruvian regulations) and, finally, the degree of association between the number of motorized vehicles transiting through the area and the concentrations of these pollutants was determined. It was concluded that there is a significant effect of schedule, location and their interaction on CO and CO2 levels. On the other hand, the concentration of CO did not exceed the Environmental Air Quality Standards. In addition, CO level was positively and weakly associated with the number of vehicles driving, while CO2 concentration was not associated with automobiles.